2021
DOI: 10.1037/vio0000377
|View full text |Cite
|
Sign up to set email alerts
|

“Serious enough”? A mixed-method examination of the minimization of sexual assault as a service barrier for college sexual assault survivors.

Abstract: Objective: Sexual assault is pervasive on college campuses, but survivors rarely use formal supports. A frequent reason that survivors do not use supports is the belief that the assault was not "serious enough." Our convergent parallel mixed method study examined the causes and consequences of minimization as a service barrier. We used qualitative interviews to examine the manifestation and impact of minimization in survivors' lives. We used quantitative surveys to examine whether minimization differed across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…All procedures were approved by the Institutional Review Board. Currently, there are four publications using these data (Holland et al., 2021a; 2020; 2021b; in press), and this paper contributes novel information about survivors’ interactions with the Title IX Office. The Title IX Office at the institution where the current study was conducted was overseen by a Title IX Coordinator and staffed several Title IX Investigators.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…All procedures were approved by the Institutional Review Board. Currently, there are four publications using these data (Holland et al., 2021a; 2020; 2021b; in press), and this paper contributes novel information about survivors’ interactions with the Title IX Office. The Title IX Office at the institution where the current study was conducted was overseen by a Title IX Coordinator and staffed several Title IX Investigators.…”
Section: Methodsmentioning
confidence: 93%
“…The sample for the current study was a subsample of students recruited from a larger mixed methods project examining cis‐straight and LGBTQ sexual assault survivors’ support seeking (for more details on the project and recruitment procedures see Holland et al., 2021). Inclusion criteria included (a) age 17 or older, (b) current undergraduate at the university, (c) plan to enroll the following semester, and (d) had an unwanted sexual experience while attending the university.…”
Section: Methodsmentioning
confidence: 99%
“…Universities must combat the stereotype that some types of sexual harassment are “not that bad,” not only because it hinders survivors from reporting (Hlavka, 2014; Holland & Cortina, 2017; Holland et al, 2021), but also because it may affect Title IX practitioners’ decision-making when survivors do report. To combat this, universities should institute trainings for Title IX staff that explicitly refute stereotypes about sexual harassment and assault and center survivors’ experiences in describing why all forms of sexual harassment are harmful and have the potential to severely limit survivors’ educations.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be an extension of what Holland et al (2021) described as "minimization barriers" in their study on student decisions reporting to Title IX officessurvivors being reluctant to report because they worried their assaults did not qualify as "severe enough." The extension of this phenomenon to student experiences with the Title IX process itself speaks to a parallel between the initial sexual trauma that the Holland et al (2021) study examined and the trauma of the Title IX process explored in this study. It also provides a potential explanation for the Fisher et al (2016) results: if complainants minimize how poorly their schools treat them, it makes sense that complainants could call their Title IX offices useful despite having a negative experience.…”
Section: Discussionmentioning
confidence: 85%
“…Limited research exists on how students going through Title IX processes at higher education institutions experience secondary victimization. Holland et al (2021) found that students identified several barriers to reporting assaults, ranging from minimizing their experiences to social-emotional barriers, though the article's discussion of minimization focused on the victimization in survivors minimizing assaults themselves. Lorenz et al (2022) examined positive and negative elements of survivor reporting experiences to Title IX offices but overlooked respondents and the role of perceived bias in student feelings.…”
Section: Previous Literature On Secondary Victimizationmentioning
confidence: 99%